Comparison of Documentation Quality using Electronic Nutrition Care Process (NUCAPRO) and Manual System - Paramita, Farah; Hartriyanti, Yayuk; ., Susestyowati; Lazuardi, Luftan (KnE Life Sciences, 2021)
Hospital nutritional care requires a timely, accurate and complete information delivery to the patients. Some barriers found in the documentation process include incomplete documentation and errors in calculating patient’s nutritional needs. We developed NUCAPRO (NCP Electronic), a computer-based system, to document the nutritional care process and help dietitians in calculating a patient’s nutritional needs. This computer system was compared with a manual system to find out which of the two provided more accurate and complete documentation. This pre-experimental study used a pre–post-test design. Eight dietitians were recruited from the Internal Medicine Department Hospital in Malang to perform the documentation of the nutritional care of 40 diabetes mellitus patients. The documentation was performed using a manual system and NUCAPRO. The completeness and accuracy of documentation were compared between the two systems. Statistical analysis was done using McNemar. The results showed no difference in terms of completeness and accuracy of documentation between the two systems (p < 0.05). However, the error in calculation using NCP Electronic was found to be lower than the manual system. We suggest developing an alert feature for the system so that the process is more efficient. Keywords: dietetics, documentation, medical informatic application, completeness, accurate, error